The Effect Of Origami-Inspired Quadrilateral Mesh On The Mechanical Behaviour Of Carbon Fiber Reinforced Silica Composite - Abd Manaf, Aiman Shaker (IRC, 2021)
Origami has end up being a hugely rich wellspring of inspiration in designing, premium in unravelling a portion of the difficulties that influence origami-inspired design and configuration has been essential.